Instrumentation at Changi land reclamation project, Singapore - Arulrajah, A.; Bo, M.; Chu, J.; Nikraz, Hamid (Thomas Telford Publishing, 2009)
Ground improvement is often required in land reclamation projects on soft soil deposits to reduce future settlement under the projected future dead and live loads. In the case of thick deposits of marine clay, it is often necessary to accelerate the consolidation process of the clay using prefabricated vertical drains. In such projects, the degree of improvement has to be ascertained to confirm whether the soil has achieved the required degree of consolidation before the removal of surcharge. This analysis can be carried out by means of observational methods for which the ground behaviour is continuously monitored from the date of instrument installation. This paper provides a case study of the applications of geotechnical instrumentation for construction control in the Changi East reclamation project in the Republic of Singapore. Field instruments adopted in this project included settlement plates, deep settlement gauges, earth pressure cells, pneumatic piezometers, electric piezometers and water standpipes. Some of the field instruments were installed offshore. Special techniques were adopted to protect these offshore instruments before placement of sand fill by hydraulic pumping. Geotechnical instruments were also used in the construction control process to monitor the deformation of ground and the stability of the earth and retaining structure.Field instrumentation readings obtained from a pilot test area comprising a vertical drain area (horizontal vertical drain spacing 1•5 m × 1•5 m) and an adjacent control area (no vertical drains) are also presented in this paper.